Why is art full of naked people? : and other vital questions about art - Hodge, Susie, ....- (London : Thames & Hudson, 2016)
Artists ask questions when they make art – and viewers ask questions when they look at art. This gently provocative book provides an engaging way for young people to start asking and answering questions for themselves. Why is art full of naked people? is structured around 22 questions, each one tackled over two spreads. The opening spread explores the question and answer, inviting the reader to study a full-bleed image of an important artwork. The second spread shows a selection of work on the theme from across history, showing how art can run with an idea to hugely different ends. The tone of the text is fresh and informal but not flippant.
Why is everything flat? What's with all the fruit? Why is art so expensive? And why do people bother with art at all?
Keywords: Kunst ; kinderen